VEHICLE DETECTOR DESIGN USING ARDUINO MICROCONTROLLER SENSOR - heryanto, tedi (Jurnal Mekanika dan Manufaktur, 2024)
ABSTRACT This research aims to create a design for a vehicle detector so that it can be applied to detect empty vehicle parking areas. This equipment can then be used in parking buildings, shopping centers, offices and hotels.The research method used is the experimental method. The results of research that has been carried out to determine the working principle of parking detection devices found that when the parking lot is full, we can immediately know. It is hoped that this research will be useful for the public, who are traveling to shopping centers, hotels and offices to provide information about parking.